2023
DOI: 10.3390/molecules28207124
|View full text |Cite
|
Sign up to set email alerts
|

Ecofriendly Synthesis of Magnetic Composites Loaded on Rice Husks for Acid Blue 25 Decontamination: Adsorption Kinetics, Thermodynamics, and Isotherms

Fozia Batool,
Samia Kanwal,
Hafsa Kanwal
et al.

Abstract: Addressing the growing need for methods for ecofriendly dye removal from aqueous media, this study explores the potential of rice husks coated with iron oxide (Fe2O3@RH composites) for efficient Acid Blue 25 decontamination. The adsorption potential of Acid Blue 25 is analyzed using raw rice husks and Fe2O3 nanoparticles in the literature, but their enhanced removal capacity by means of Fe2O3@RH composites is reported for the first time in this study. Fe2O3@RH composites were analyzed by using analytical techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…In this work, IONPs synthesized by co-precipitation were used for the selective removal of chlorophyll from the extract of green plants. The spectra obtained in the SEM-EDS study were similar to those reported in previous works [ 38 , 59 ], which confirms the reliability and repeatability of this synthesis method. The synthesized IONPs had magnetic properties.…”
Section: Discussionsupporting
confidence: 88%
“…In this work, IONPs synthesized by co-precipitation were used for the selective removal of chlorophyll from the extract of green plants. The spectra obtained in the SEM-EDS study were similar to those reported in previous works [ 38 , 59 ], which confirms the reliability and repeatability of this synthesis method. The synthesized IONPs had magnetic properties.…”
Section: Discussionsupporting
confidence: 88%
“…Natural waters contaminated with dyes have limited transparency, which results in the inhibition of photosynthesis carried out by autotrophic aquatic organisms [ 1 ]. A significant proportion of the dyes are toxic to aquatic organisms [ 2 ], which, combined with the reduced oxygen content in the water reservoir, may diminish ecosystem’s biodiversity.…”
Section: Introductionmentioning
confidence: 99%